A broad view of precocious reading. (21st February 2021) - Bergman Deitcher, Deborah; Aram, Dorit; Besser‐Biron, Shira
Abstract : Background: Precocious readers (PRs) are children who read and comprehend fluently in their native language, without receiving formal instruction. This study examined Hebrew‐speaking PRs in comparison with a group of age‐matched peers and a group of reading‐level‐matched peers. By examining Hebrew, which is a transparent orthography when it has diacritics and opaque without the diacritics, the study aimed to expand our understanding of PRs and shed light on universal and orthographic‐specific aspects of precocious reading. Additionally, language and math are both code‐based systems, yet previous studies largely neglected assessing PRs' math skills. Studying these skills can highlight the process of reading as a symbol system that needs decoding and further clarify its relationship with other symbol‐based systems. Methods: We examined 20 PRs who were matched with 20 same‐age preschoolers. Additionally, to compare the PRs with a group exposed to formal reading instruction, we matched them with 20 older children with the same reading level. We studied the three groups' language, letter knowledge, phonological awareness, reading, writing and math skills. Hierarchical regression analyses were used to examine differences between the groups on these measures, controlling for nonverbal intelligence. Results: Beyond the contribution of nonverbal intelligence, being in the PR group conferred a significant advantage over the same‐age group on almost all measured skills. The PRs scored similarly to the same reading level group on letter knowledge and phonological awareness, significantly outperformed them on word reading and nearly on math ( p = .06) but scored lower than them on writing and vocabulary. Conclusions: This study promotes the understanding of precocious reading beyond a particular orthography. It highlights reading development as an act of deciphering symbols, thereby relating it to other symbol systems such as math. Being aware of PRs' skills can help parents and educators adequately support these children.